Pengaruh Likuiditas, Profitabilitas, dan Struktur Modal Terhadap Nilai Perusahaan (Studi Kasus pada Jakarta Islamic Indeks Sebelum dan Masa Pandemi) - Attien Rahmawati Ade Suryani; Wafiatun Mukharomah (Universitas Muhammadiyah Surakarta, 2023)
This research was conducted to determine the difference before and during the pandemic to companies value by using a sample of the Jakarta Islam Index (JII) listed on the Indonesia Stock Exchange in the 2018-2021 period. The research method used by researcher was the Paired Sample t-Test. This study shows that the Covid-19 pandemic has a bad enough impact on the capital market. Based on the results of the Paired Samples t-Test that has been carried out, it can be concluded that before and during the Covid-19 pandemic the Current Ratio variable did not have a significant effect on the company value, so that it can be said that there was no difference between before and during the Covid-19 pandemic. For the Return on asset and Debt to Equity Ratio variables have a significant influence on the company value, it can be said that there is a difference between before and during the Covid-19 pandemic.